Challenges encountered with a mindfulness app: Lessons learnt from a pilot randomized trial involving caregivers and individuals with autism. (August 2022) - Hartley, Matthew; Dorstyn, Diana; Due, Clemence
Abstract: Background: We undertook a trial to examine the feasibility of a self-guided mindfulness app, Smiling Mind, for children and adults with Autism Spectrum Disorder (ASD) and their parents. The trial encountered problems in recruitment, enrollment and retention which are described here. Methods: : Of 169 eligible participants, only 22 consented and were randomly assigned to Smiling Mind ( n = 12) or an attention control condition ( n = 10). A further six participants withdrew during the study. Barriers to trial participation were subsequently explored through semi-structured interviews, to form case studies, and a follow-up survey. Results: Interview and survey data highlighted parents' competing time commitments as a key barrier to participation. For children and adults with ASD, distraction and boredom were major challenges to engagement. Conclusions: A number of modifiable variables in our recruitment procedures and intervention design ultimately resulted in a sample size that was too small to draw any firm conclusions from. Future ASD research can maximize sampling by broadening recruitment strategies and partnering with community services and schools. Engagement in mindfulness could also be improved by incorporating regular communication to motivate time poor participants. Highlights: Partnering with primary care and education providers may improve recruitment Time and competing demands inhibited trial participation. Distraction during meditation exercises was a key issue for individuals with ASD. Strategies to engage app users and ensure repeat usage are needed.